2002
DOI: 10.1038/sj.onc.1205778
|View full text |Cite
|
Sign up to set email alerts
|

Novel target for induction of apoptosis by cyclo-oxygenase-2 inhibitor SC-236 through a protein kinase C-β1-dependent pathway

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) reduce the risk of gastrointestinal cancers. Recently, a similar protective effect has been demonstrated by the specific cyclo-oxygenase-2 (COX-2) inhibitors. However, the exact mechanism that accounts for the anti-proliferative effect of specific COX-2 inhibitors is still not fully understood, and it is still controversial whether these protective effects are predominantly mediated through the inhibition of COX-2 activity and prostaglandin synthesis. Identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 57 publications
(59 reference statements)
4
50
0
Order By: Relevance
“…The protein kinase C family has crucial regulatory roles in cell growth and cell-cycle progression (Frey et al, 1997;Ashton et al, 1999;Jiang et al, 2002;Deeds et al, 2003;Cerda et al, 2006). Various studies have shown that PKC suppression generally inhibits cell-cycle progression, whereas PKC activation stimulates cellcycle progression (Frey et al, 1997;Deeds et al, 2003;Cerda et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The protein kinase C family has crucial regulatory roles in cell growth and cell-cycle progression (Frey et al, 1997;Ashton et al, 1999;Jiang et al, 2002;Deeds et al, 2003;Cerda et al, 2006). Various studies have shown that PKC suppression generally inhibits cell-cycle progression, whereas PKC activation stimulates cellcycle progression (Frey et al, 1997;Deeds et al, 2003;Cerda et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The proapoptotic effects of Cox-2 inhibitors are well documented (Sawaoka et al, 1998;Jiang et al, 2002). In non-small-cell lung cancer cell lines, genetic or pharmacological inhibition of Cox-2 enhances proteosomal degradation of the inhibitor of apoptosis survivin (Beltrami et al, 2004;Krysan et al, 2004a, b).…”
Section: Cycloxygenase-2 Inhibitors Tp53 Mutations and Druginduced Amentioning
confidence: 99%
“…For example, a COX-2-selective inhibitor celecoxib exerted synergistic antitumor effects when combined with gemcitaine or 5-fluorouracil in patients with advanced pancreatic cancer (2), and it enhanced the response to paclitaxel and carboplatin in early-stage non -small cell lung cancer (3). The mechanism underlying the antitumor activity of COX-2 inhibitors is thought to involve inhibition of COX-2 enzyme activity and induction of apoptosis, but it is unclear whether COX-2 inhibition is required to induce apoptosis (4).…”
Section: Introductionmentioning
confidence: 99%